Towards a cross platform solution to share small scale data across smart–devices using audio waves: a prototype development in android environment - Hasan, S. M. Ferdous; Murshed, Adnan Bin; Hayat, Ahrar (BRAC Univeristy, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Electronic and Communication Engineering & Electrical and Electronic Engineering, 2016.